Anaerobic ammonium oxidation coupled to arsenate reduction, a novel biogeochemical process observed in arsenic-contaminated paddy soil. (15th October 2022) - Zhang, Miaomiao; Kolton, Max; Häggblom, Max M.; Sun, Xiaoxu; Yu, Ke; He, Bin; Yuan, Zaijian; Dong, Yiran; Su, Xianfa; Chen, Zhenyu; Li, Hui; Xiao, Tangfu; et al.
Abstract: Anaerobic ammonium oxidation represents an important pathway of N loss, which can be coupled with reduction of nitrite and metal(loid)s (e.g., Fe(III) and Mn(IV)). Similar to Fe(III) and Mn(IV), As(V) is also an active metal(loid) and ammonium oxidation coupled with As(V) reduction is thermodynamically feasible. However, little is known about this potential process. In this study, anaerobic ammonium oxidation coupled with As(V) reduction, designated as Asammox, was observed in cultures inoculated from As-contaminated paddy soil using 15 N isotope tracer analysis. Compared with the treatment amended with 15 N-urea only, the production of 15 N-labeled N2 (i.e., 30 N2 and 29 N2 ) was significantly greater in the treatment amended with As(V) and 15 N-urea. Furthermore, the abundances of the genes encoding for arsenate reductase ( arrA ) and hydrazine synthase ( hzsB ) were significantly higher in the treatment amended with As(V) and 15 N-urea than those in the treatment amended with 15 N-urea only. In addition, putative Asammox bacteria affiliated with Halomonas, Pelagibacterium, and Chelativorans were identified by DNA-stable isotope probing. Members of Ca. Brocadia were the most dominant Anammox bacteria in the soil cultures and may interact with Asammox bacteria in ammonium oxidation, suggesting that the N loss may be attributed to the contribution of Asammox and Anammox in the As-contaminated soil. The observation of Asammox, a novel biogeochemical process, and identification of bacteria responsible for this biogeochemical process expands the fundamental understanding of both N and As biogeochemical cycling. In addition, this study provides a proof-of-concept for investigating anaerobic ammonium oxidation coupled with metal(loid)s reduction by combining stable isotope probing and isotope tracer microcosm incubations.